Pembentukan Disiplin Santri dengan Pembiasaan dalam Teori Behavioristik di TK Ummatan Wahidah Curup - Beni Azwar (Universitas PGRI Semarang, 2023)
AbstractThis study aims to determine the formation of student discipline with habituation in Behavioristic theory at Ummatan Wahidah Curup Kindergarten. This is based on the fact that this school is an Islamic kindergarten with 2 curriculum contents (National Education and Ministry of Religion) which requires more time and energy in disciplining students so that the curriculum targets can be achieved, while the age is only 4-6 years old.The research method used is mix-method by combining quantitative and qualitative methods, the data will be revealed quantitatively and explored qualitatively, then will be presented descriptively. Data analysis techniques by collecting and reviewing the results of questionnaires, interviews and documentation, then after triangulation techniques and data reduction, the data is presented descriptively.The results of research from 16 Ummatan Wahidah Kindergarten teachers 84% understand the importance of discipline habituation in learning Ummatan Wahidah Curup Kindergarten students. The application of rewards in forming habituation is more dominant by giving stars as prizes and verbal praise, while punishment is replaced by strict educational actions, the highest discipline in learning is seen in prayer and recitation, the formation of discipline is more effective with Islamic values and the role of parents and ustad / ustadzah in providing examples and can be emulated.Keywords: Dicipline Formation; Habituation dan Behavioristic TheoryAbstrakPenelitian ini bertujuan untuk mengetahui pembentukan disiplin santri dengan pembiasaan dalam teori Behavioristik di TK Ummatan Wahidah Curup. Hal ini didasari bahwa sekolah ini merupakan TK Islam dengan 2 muatan kurikulum (Pendidikan Nasional dan Kementerian Agama) yang membutuhkan waktu dan tenaga yang lebih dalam mendisiplinkan siswa agar target kurikulum dapat tercapai, sementara usianya baru 4 – 6 tahun.Metode penelitian yang digunakan mix-method dengan menggabungkan metode kuantitatif dan kualitatif, data akan diungkapkan secara kuantitatif dan didalami secara kualitatif, kemudian akan dipaparkan secara deskriptif. Teknik Analisa data dengan mengumpulkan dan menelaah hasil angket, wawancara dan dokumentasi, kemudian setelah triangulasi Teknik dan reduksi data, maka data disajikan secara deskriptif.Hasil penelitian dari 16 orang guru TK Ummatan Wahidah 84 % memahami pentingnya pembiasaan disiplin dalam belajar santri TK Ummatan Wahidah Curup. Penerapan reward dalam membentuk pembiasaan lebih dominan dengan pemberian bintang sebagai hadiah dan pujian verbal, sedangkan punishment diganti dengan tindakan tegas mendidik, disiplin tertinggi dalam belajar terlihat pada berdoa dan mengaji, pembentukan disiplin lebih efektif dengan nilai-nilai Islami dan peran orang tua dan ustad/ustadzah dalam memberikan contoh dan dapat dicontoh.Kata kunci: Pembentukan Disiplin; Pembiasaan dan Teori Behavioristik